Role-identity and role-variability as factors of harmonious development of personality - Odintsova, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
In the given article is attempt to consider the role of identity and role variability, as factors that direct the individual to a more complete and profound development. The concept of the "vital role" is revealed through such concepts as: "life script", "attitude", "life line", "the strategy of life" and "life perspective".